Synthesis of lactones from tetrahydrofuran derivatives and study of some translactonisation reactions - McCarthy, Una (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
The research undertaken in the present study focuses on the synthesis of lactones via the intramolecular acylative cleavage reactions of tetrahydroflirain derivatives. The thesis is divided into a number of sections: an introduction describing the principle characteristics of, and synthetic routes to medium- and large-ring lactones; studies on intramolecular reactions of 3-(tetrahydro-2'-furyl) propanoic acid; synthesis of some ring-enlarged lactones via translactonisation processes; and studies towards the development of a synthetic route to the precursors required for the synthesis of two naturally-occurring lactones
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin